Tailoring pore structures and morphologies of highly ordered cubic mesoporous silica prepared in mild conditions: the effects of reaction parameters - Silveira, Roberto Medeiros; Almeida, Everton Rodrigues de; Ospina, Carlos Alberto; Castro, Gustavo Rocha de [UNESP]; Verelst, Marc; Utrera Martines, Marco Antonio (Springer, 2021)
In this study, we report on a novel and reactive synthesis of highly ordered cubic mesoporous silica that is able to tailor different symmetries of pores and morphologies through a two-step procedure carried out in relatively low temperatures (20-60 degrees C) using a single type of surfactant. We systematically examined the effects of reaction parameters such as pH, times of hydrolysis and condensation, concentration of Pluronic F-127 surfactant, and aging temperature, by using characterization techniques such as small-angle X-ray scattering (SAXS), analysis of surface area and porosity by adsorption of N-2 (BET isotherms), and scanning and transmission electron microscopy (SEM and TEM). Our investigations found that, at 20 degrees C, the shape of particles is sensitive to changes in surfactant concentration which means that it is possible to tune spherical to polyhedral particles by simply increasing the amount of surfactant. In addition, at low concentrations of F-127, the size of the particles is temperature-dependent, with an inversely proportional pattern of behavior. The protocol also enables the production of well-ordered pores, particularly with 3D-cubic symmetries Fm3m and Im3m, and some hexagonal, as well as to control the sizes of the pores.
Keywords: Cubic mesoporous silica; Polyhedral particles; Pluronic F-127; Morphology tuning; Reaction parameters